2008
DOI: 10.1016/j.neuron.2008.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Different Dynamics of Performance and Brain Activation in the Time Course of Perceptual Learning

Abstract: Perceptual learning is regarded as a manifestation of experience-dependent plasticity in the sensory systems, yet the underlying neural mechanisms remain unclear. We measured the dynamics of performance on a visual task and brain activation in the human primary visual cortex (V1) across the time course of perceptual learning. Within the first few weeks of training, brain activation in a V1 subregion corresponding to the trained visual field quadrant and task performance both increased. However, while performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
312
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(364 citation statements)
references
References 31 publications
(51 reference statements)
40
312
2
2
Order By: Relevance
“…Interestingly, training on orthogonal contours resulted in a smaller but significant behavioral improvement for collinear contours that was associated with decreased activations for collinear contours in temporal and frontoparietal regions. These results are consistent with previous imaging studies showing decreased fMRI activations for training of salient stimuli for which performance has saturated (Kourtzi et al 2005;Yotsumoto et al 2008) that may relate to a more efficient stimulus representation by smaller neural ensembles. Finally, no significant learning-related changes were observed for acute contours, consistent with the lack of learning transfer for these contour stimuli for the training period used in this study (see also Schwarzkopf and Kourtzi 2008).…”
Section: Training-dependent Changes In Activation Magnitude: Intact Vsupporting
confidence: 92%
“…Interestingly, training on orthogonal contours resulted in a smaller but significant behavioral improvement for collinear contours that was associated with decreased activations for collinear contours in temporal and frontoparietal regions. These results are consistent with previous imaging studies showing decreased fMRI activations for training of salient stimuli for which performance has saturated (Kourtzi et al 2005;Yotsumoto et al 2008) that may relate to a more efficient stimulus representation by smaller neural ensembles. Finally, no significant learning-related changes were observed for acute contours, consistent with the lack of learning transfer for these contour stimuli for the training period used in this study (see also Schwarzkopf and Kourtzi 2008).…”
Section: Training-dependent Changes In Activation Magnitude: Intact Vsupporting
confidence: 92%
“…First, we provide evidence for learning-dependent changes related to neural sensitivity rather than simply overall responsiveness (i.e., increased or decreased fMRI responses) to trained stimuli as reported in previous imaging studies (Kourtzi et al, 2005;Sigman et al, 2005;Op de Beeck et al, 2006;Mukai et al, 2007;Yotsumoto et al, 2008). This previous work does not allow us to discern whether learningdependent changes in fMRI signals relate to changes in the overall magnitude of neural responses or changes in neuronal selectivity of neural populations.…”
Section: Discussionmentioning
confidence: 64%
“…We suggest that, because of this, large neural networks that include low-to high-level areas may play a role in offline consolidation from the beginning of learning (Lewis et al, 2009). Reports of changes in stimulus-driven activation observed with fMRI early in visual skill learning (Schwartz et al, 2002;Mukai et al, 2007;Yotsumoto et al, 2008), of reverberating activity in large functional networks after a learning experience (Hoffman and McNaughton, 2002;Ji and Wilson, 2007;Tambini et al, 2010), and of behavioral interference early in visual learning (Seitz et al, 2005) all support this possibility. Interfering input, such as delivered by TMS, may reset the synaptic weights of readout routines more easily when the network that maintains them is smaller (Buonomano and Maass, 2009) and does not include high-level areas that during offline consolidation may help strengthening the synaptic weights appropriate for the task (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Training-induced response changes have been shown after prolonged training (Schoups et al, 2001) but also after a single training session (Schwartz et al, 2002;Yotsumoto et al, 2008). Moreover, human neuroimaging (Yotsumoto et al, 2009) has revealed offline V1 activity during sleep 6 h after a single session of visual skill learning, implicating V1 in offline consolidation after a small amount of training.…”
Section: Introductionmentioning
confidence: 99%